Acute Renal Replacement Therapy in Children with Diarrhea-Associated Hemolytic Uremic Syndrome: A Single Center 16 Years of Experience - Silviu Grisaru; Melissa A. Morgunov; Susan M. Samuel; Julian P. Midgley; Andrew W. Wade; James B. Tee; Lorraine A. Hamiwka (International Journal of Nephrology)
Acute kidney injury (AKI) is becoming more prevalent among hospitalized children, its etiologies are shifting, and new treatment modalities are evolving; however, diarrhea-associated hemolytic uremic syndrome (D+HUS) remains the most common primary disease causing AKI in young children. Little has been published about acute renal replacement therapy (ARRT) and its challenges in this population. We describe our single center's experience managing 134 pediatric patients with D+HUS out of whom 58 (43%) required ARRT over the past 16 years. In our cohort, all but one patient were started on peritoneal dialysis (PD). Most patients, 47 (81%), received acute PD on a pediatric inpatient ward. The most common recorded complications in our cohort were peritoneal fluid leaks 13 (22%), peritonitis 11 (20%), and catheter malfunction 5 (9%). Nine patients (16%) needed surgical revision of their PD catheters. There were no bleeding events related to PD despite a mean platelets count of 40.9 (±23.5) × 103/mm3 and rare use of platelets infusions. Despite its methodological limitations, this paper adds to the limited body of evidence supporting the use of acute PD as the primary ARRT modality in children with D+HUS.